Metformin therapy before conception versus throughout the pregnancy and risk of gestational diabetes mellitus in women with polycystic ovary syndrome: a systemic review, meta-analysis and meta-regression - Razieh Bidhendi Yarandi; Samira Behboudi-Gandevani; Mina Amiri; Fahimeh Ramezani Tehrani (Diabetology & Metabolic Syndrome, 2019)
Abstract The results of studies that assessed the impact of metformin treatments on gestational diabetes mellitus (GDM) in patients with polycystic ovary syndrome (PCOS) are inconclusive. In addition, the impact of time and duration of metformin therapy for an optimum reduction of GDM has not been reported in these studies. This study aimed to summarize current knowledge regarding the effect of metformin-therapy before conception versus throughout pregnancy on the risk of GDM in women with PCOS. PubMed, Scopus, Google Scholar and ScienceDirect databases were searched to identify relevant studies. Both fixed and random effect models were used. Subgroup analyses were performed based on the on the study methodology. The association between the PCOS status and GDM was assessed using the univariate and multiple meta-regression analysis adjusted by the BMI and metformin therapy. Forty-eight of 1397 identified studies were included involving 5711 PCOS patients and 20,296 controls. Regardless of metformin therapy, the prevalence of GDM diagnosed in the second trimester among women with PCOS was significantly higher than healthy controls that was independent of obesity. Including all studies, the increased risk of GDM among women with PCOS, compared to healthy controls, disappeared after the adjustment of metformin-therapy (β = 0.08, 95% CI 0.04, 0.2; p = 0.624). By excluding observational studies as a source of bias, the prevalence of GDM among women with PCOS treated using metformin before conception till the end of pregnancy did not differ from treated just before conception (β = − 0.09, 95% CI − 0.2, 0.02; p = 0.092) or those without metformin therapy (β = − 0.05, 95% CI − 0.07, 0.04; p = 0.301). The results remained unchanged after the subgroup analysis based on the methodology of RCTs and non-RCTs studies. The main body of literature in the current meta-analysis was observational, which may be mixed with some sources of bias. Also, a lack of well-designed and high quality interventional studies means that the findings should be interpreted with cautious. In this respect, decisions regarding the continuation or discontinuation of metformin therapy in women with PCOS are somewhat arbitrary and can be made individually based on the patient’s condition given the presence or absence of other GDM risk factors. Additional well-designed RCTs still need for precise recommendation.